2021
DOI: 10.1021/acs.est.1c03875
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical Production by Air Pollutants in Epithelial Lining Fluid Governed by Interconversion and Scavenging of Reactive Oxygen Species

Abstract: Air pollution is a major risk factor for human health. Chemical reactions in the epithelial lining fluid (ELF) of the human respiratory tract result in the formation of reactive oxygen species (ROS), which can lead to oxidative stress and adverse health effects. We use kinetic modeling to quantify the effects of fine particulate matter (PM2.5), ozone (O 3 ), and nitrogen dioxide (NO 2 ) on ROS formation, interconversion, and reactivity, and discuss different chemical metrics for oxidative stress, such as cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 86 publications
2
104
3
Order By: Relevance
“…The ozonolysis of alkenes is not only important for atmospheric chemistry but also for human health . Cell membranes and the lipid layer on top of the epithelial lining fluid contain unsaturated compounds and are exposed to ozone. This study and other recent studies , point toward a large amount of reactive intermediates and radicals generated in alkene ozonolysis which might give rise to lipid peroxidation and in vivo production of hazardous reactive (oxygen) species. Thus, due to the wealth of data that are already available for oleic acid ozonolysis, it is a particularly useful reaction system to use in conjunction with kinetic modeling and draw conclusions regarding health effects of air pollution.…”
Section: Discussionmentioning
confidence: 68%
“…The ozonolysis of alkenes is not only important for atmospheric chemistry but also for human health . Cell membranes and the lipid layer on top of the epithelial lining fluid contain unsaturated compounds and are exposed to ozone. This study and other recent studies , point toward a large amount of reactive intermediates and radicals generated in alkene ozonolysis which might give rise to lipid peroxidation and in vivo production of hazardous reactive (oxygen) species. Thus, due to the wealth of data that are already available for oleic acid ozonolysis, it is a particularly useful reaction system to use in conjunction with kinetic modeling and draw conclusions regarding health effects of air pollution.…”
Section: Discussionmentioning
confidence: 68%
“…The environmental implication is that inhalation of aerosols containing SOZs and transition metal ions may induce oxidation of antioxidants in the epithelial lining fluid. 6 , 57 This would result in disruption of the redox balance of the human respiration system. Furthermore, the present demonstration that terpenoid-derived SOZs can be stable in the aqueous phase hints at the potential use of rationally designed SOZs as antibacterial drugs.…”
Section: Resultsmentioning
confidence: 99%
“…3 A), which is attributable to the oxidizing action arising from the redox-active components nitrogen dioxide, sulfur dioxide, ozone, etc. in GEEG [ 24 , 25 ]. In the subsequent anti-GEEG activity evaluation by pretreating SC with the test samples, we found that SFE was also active against GEEG-induced protein carbonylation in the SC (Fig.…”
Section: Discussionmentioning
confidence: 99%